The littoral sea cucumbers (Echinodermata: Holothuroidea) of Guam re-assessed – a diversity curve that still does not asymptote - Michonneau , Francois; Borrero-Perez, Giomar Helena; Honey, Magali; Kamarudin, Kamarul Rahim; Kerr, Alexander M.; Kim, Sun-Ju; Menez, Marie Antonette; Miller, Allison; Ochoa, Julio Adrian; Olavides, Ronald D.; Paulay, Gustav; Samyn, Yves; et al. (Cahiers de Biologie Marine, 2013)
The Micronesian island of Guam has been an important site for the study of littoral tropical holothurian taxonomy for almost 200 years. Despite substantial attention by both expeditions and resident taxonomists, new records are still regularly added to the fauna, demonstrating the challenge of documenting even such large and well-known animals in a small hyper-diverse area. Guam is the type locality of species described by Quoy & Gaimard (1833) and Brandt (1835). A survey of the sea cucumber fauna by Rowe & Doty (1977) led to one of the most used guides for the identification of tropical Pacific sea cucumbers because of the color illustrations of living animals it presented. Focus on echinoderms including holothurians continued with numerous new records added in the following decades. Paulay (2003a) summarized the fauna last, recording 46-47 species. At this stage the fauna was thought to be well documented. A week-long workshop on holothurian systematics sponsored by the National Science Foundation PEET (Partnerships for Enhancing Expertise in Taxonomy) project in 2010 included a substantial field work component, sampling both during the day and night, with snorkeling and SCUBA, across a variety of habitats. This survey yielded 40 species, including numerous new records and even species. Further sampling by Kerr’s lab since the workshop has added additional records. The littoral holothuroid fauna of Guam now comprises 65 species in 17 genera and 7 families. Half of the 19 newly recorded species are the result of unravelling cryptic species in complexes, the other half are based on new collections. Eleven species are known from single specimens, suggesting that much still remains to be learned about the fauna.